Efek Leverage Dan Besaran Perusahaan Pada Manajemen Laba Melalui Pengungkapan Social Responsibility - Sofia Prima Dewi (Jurnal Ekonomi, 2021)
The purpose of this study is to obtain empirical evidence whether leverage has a positive effect on earnings management, whether the company size and social responsibility disclosure has a negative impact on earnings management, whether the company size has a positive impact on social responsibility disclosure, and whether the social responsibility disclosure can mediate the impact of company size on earnings management. The sampling technique used was purposive sampling and Smart PLS 3.0 was used for data processing. Research during the 2017-2019 period on 72 companies shows that leverage does not have a positive impact on earnings management, company size has a negative impact on earnings management, company size has a positive impact on social responsibility disclosure, social responsibility disclosure has no negative impact on earnings management, and social responsibility disclosure cannot mediate the impact of company size on earnings management.